Characterization of Badinsk Zeolite and its Use for Removal of Phosphorus and Nitrogen Compounds from Wastewater; Materials Science Forum; Vol. 970 : Modern Problems in Materials Processing, Manufacturing, Testing and Quality Assurance II - Novikova A. Anastasiya; Nazarenko O. B. Olga Bronislavovna; Vtorushina A. N. Anna Nikolaevna; Zadorozhnaya T. A. Tatiyana Anatolyevna (2019, 2019)
Title screen